2016
DOI: 10.1111/jop.12438
|View full text |Cite
|
Sign up to set email alerts
|

Immunoexpression of hoxb7 and hoxb9 in salivary gland tumours

Abstract: Background: Salivary gland carcinomas are uncommon neoplasms and the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…A number of studies have shown that HOXB7 is abnormally expressed in a variety of solid tumors including oral squamous cell carcinoma (OSCC), colon cancer, breast cancer, esophageal cancer, pancreatic cancer, lung cancer, gastric cancer, and liver cancer [16] . However, the development and outcome of the disease caused by this abnormal expression are not always consistent, which is manifested in: Although most studies have supported the conclusion that abnormally high expression of HOXB7 was related to worse survival of the patients, there are still several studies with different results showing a correlation trend but without statistical significance between high expression of HOXB7 and poorer survival of salivary gland tumor patients, OSCC patients, and gastric cancer patients [17–19] . However, there were some shortcomings in these 3 studies, such as the pathological types were mixed with benign and malignant tumors, which resulted in the different treatment options, most of the included patients were in stage III/IV and insufficient of sample size as well as follow-up time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have shown that HOXB7 is abnormally expressed in a variety of solid tumors including oral squamous cell carcinoma (OSCC), colon cancer, breast cancer, esophageal cancer, pancreatic cancer, lung cancer, gastric cancer, and liver cancer [16] . However, the development and outcome of the disease caused by this abnormal expression are not always consistent, which is manifested in: Although most studies have supported the conclusion that abnormally high expression of HOXB7 was related to worse survival of the patients, there are still several studies with different results showing a correlation trend but without statistical significance between high expression of HOXB7 and poorer survival of salivary gland tumor patients, OSCC patients, and gastric cancer patients [17–19] . However, there were some shortcomings in these 3 studies, such as the pathological types were mixed with benign and malignant tumors, which resulted in the different treatment options, most of the included patients were in stage III/IV and insufficient of sample size as well as follow-up time.…”
Section: Discussionmentioning
confidence: 99%
“…[16] However, the development and outcome of the disease caused by this abnormal expression are not always consistent, which is manifested in: Although most studies have supported the conclusion that abnormally high expression of HOXB7 was related to worse survival of the patients, there are still several studies with different results showing a correlation trend but without statistical significance between high expression of HOXB7 and poorer survival of salivary gland tumor patients, OSCC patients, and gastric cancer patients. [17][18][19] However, there were some shortcomings in these 3 studies, such as the pathological types were mixed with benign and malignant tumors, which resulted in the different treatment options, most of the included patients were in stage III/IV and insufficient of sample size as well as follow-up time. Several studies showed that the correlation between high expression of HOXB7 and survival of the patients only existed in the subtypes of certain tumors.…”
Section: Hoxb7mentioning
confidence: 99%
“…Understanding the tumorigenesis of aggressive neoplasms in salivary glands is essential to improving the clinical management of these rare tumors, and identifying new prognostic markers is key to this understanding. 1,2 As a member of the TNF super family, RANKL plays an important role in the formation, function, survival, and bone resorption of osteoclasts, and is often responsible for osteoclastogenesis in bone metastases of malignant tumors. 14 While RANKL inhibitors have successfully treated bone-related pathologies such as osteoporosis, bone metastases, and giant cell tumors of the bone, a recent study has investigated the usability of the RANKL inhibitor in breast tumors.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the pathogenesis and molecular basis of these tumors are not well understood due to their complexity. 1,2 The receptor activator of nuclear factor kB ligand (RANKL) is a tumor necrosis factor (TNF) superfamily protein expressed in the surface of osteoblasts and bone marrow stromal cells and is present in carcinomas of various types. It plays a key role in the production, function, and survival of osteoclasts by binding to its own receptor, receptor activator of nuclear factor kB (RANK), which is expressed on the surface of myeloid osteoclast precursors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation